A simplified estimation approach for service life of steel bar within concrete. (March 2019) - Tu, Xi; Di, Jin; Zhang, Peng; Qin, Fengjiang
Evaluating corrosion of steel bars within concrete cross section was the major task for durability of reinforced concrete structures. Although plenty of steel bars with various boundary condition caused huge computation load in numerical simulation, most of them were in different geometric locations while their other configuration was similar, such as temperature, moisture, and concrete composition. In this article, shape-based estimation approach was introduced for simplifying assessment of durability of concrete structures regarding numerical simulation. Based on the same penetration condition and diffusing media, the similarity of geometric configuration was the primary consideration of shape-based estimation and a mathematic model regarding the length of involving outline within a circular region with given radius was proposed. The crossbeam of an aged reinforced concrete arch bridge in coastal area was assessed, based on which shape-based estimation was proved to be applicable by comparing with finite element analysis. An evaluating tools called Weighed Corrosion Index in terms of corrosion degree of rebar in the whole concrete section was proposed and discussed in the application on degradation of concrete members. Moreover, for the purpose of modeling and post-processing, designed rebar within concrete section might not be exactly occupied by the nodes of meshed section and thus, content of aggressive agent cannot be directly obtained. An approach for identifying of rebar position and interpolating the content at rebar position was introduced.